Enhancing English Writing Skills Through Culturally Relevant Texts: An Experimental Study in Banten EFL Learners - Arifin, M. Nur (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
Writing is often considered one of the most challenging aspects of language learning because it requires a strong understanding of grammar, a broad vocabulary mastery, and high syntactic abilities. This study examines the influence of local culture-based texts on improving students' writing skills in Banten. With a quasi-experimental design involving 35 students in the experimental and control groups, data was collected through pre-test and post-test tests, questionnaires, and observations. The results showed a significant improvement in the experimental group (mean -32.571, SD 5.987, p < 0.001), with students showing high motivation (mean 4.3) and satisfaction with the material (mean 4.2). Observation recorded increased interactions, such as discussion empathy (3.5 to 4.6). These findings confirm that local culture-based texts improve students' writing skills, motivation, and collaboration. The research implications include the development of cultural-based contextual learning strategies to support the Independent Curriculum, improve linguistic competence, and strengthen students' cultural identity.